Comprehensive comparison of two protein family of P-ATPases (13A1 and 13A3) in insects. (June 2017) - Seddigh, Samin
Graphical abstract: Highlights: The proteomics analysis of two P-ATPase families including P-ATPase 13A1 and P-ATPase 13A3 was performed for the first time in different insect species. Seventeen similar domains obtained by functional analysis of insect P-ATPase families which showed similarities among them. KEGG pathways were obtained by protein–protein interaction among two different P-ATPase families.. Phylogenetic tree of different P-ATPase insect species was designed which can be the basis of phylogenetic studies. These proteomics analyses provide background of bioinformatic studies for the function and evolution of this enzyme in insects. Abstract: The P-type ATPases (P-ATPases) are present in all living cells where they mediate ion transport across membranes on the expense of ATP hydrolysis. Different ions which are transported by these pumps are protons like calcium, sodium, potassium, and heavy metals such as manganese, iron, copper, and zinc. Maintenance of the proper gradients for essential ions across cellular membranes makes P-ATPases crucial for cell survival. In this study, characterization of two families of P-ATPases including P-ATPase 13A1 and P-ATPase 13A3 protein was compared in two different insect species from different orders. According to the conserved motifs found with MEME, nine motifs were shared by insects of 13A1 family but eight in 13A3 family. Seven different insect species from 13A1 and five samples from 13A3 family were selected as the representative samples for functional and structural analyses. The structural and functional analyses were performed with ProtParam, SOPMA, SignalP 4.1, TMHMM 2.0, ProtScale and ProDom tools in the ExPASy database. The tertiary structure of Bombus terrestris as a sample of each family of insects were predicted by the Phyre2 and TM-score servers and their similarities were verified by SuperPose server. The tertiary structures were predicted via the "c3b9bA" model (PDB Accession Code:3B9B ) in P-ATPase 13A1 family and "c2zxeA" model (PDB Accession Code:2ZXE ) in P-ATPase 13A3 family. A phylogenetic tree was constructed with MEGA 6.06 software using the Neighbor-joining method. According to the results, there was a high identity of P-ATPase families so that they should be derived from a common ancestor however they belonged to separate groups. In protein–protein interaction analysis by STRING 10.0, six common enriched pathways of KEGG were identified in B. terrestris in both families. The obtained data provide a background for bioinformatic studies of the function and evolution of other insects and organisms.